PERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA YOUTUBE DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 1, TIGALINGGA - Agita Karina Sinulingga; Sadieli Telaumbanua; Yenita Br Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of YouTube itself as an efficient learning method between students andteachers This study aims to determine Students Perceptions Of The Use OfYoutube Media In Improving The Negotiation Text Writing Skills Of Students InClass X Of Sma Negeri 1 Tigalingga. The issues addressed in this study arestudents perceptions of YouTube and the use of YouTube in improvingnegotiation text writing skills. The results indicate that students have a positiveperception of YouTube as a learning method in addition to teachers and textbooks.This is evident in the level of success students achieved in writing negotiation textsafter watching and understanding lessons through YouTube. This study employeda descriptive qualitative method, with data collection conducted through fouraspects: appeal, relevance, effectiveness, and motivation. Data was obtainedthrough observation, interviews, and documentation. The research results show animprovement in students skills in writing negotiation texts after watching lessonsthrough YouTube. Additionally, there were positive responses regarding theaspects of appeal, relevance, effectiveness, and motivation toward in conductingthe teaching-learning process.